Engaging Students With Social Media. (December 2015) - Bal, Anjali S.; Grewal, Dhruv; Mills, Adam; Ottley, Gary
The importance of social media for marketing professionals has grown immensely as consumers turn to it to connect with products, brands, and brand communities. Yet limited research investigates the uses of social media to teach core marketing concepts. This article analyzes coursework in foundational marketing classes, with a specific focus on the effectiveness of social media for teaching core marketing concepts. Through the use of multiple social media platforms, the courses sought to engage students in active learning and provide a medium for the students to apply marketing concepts and market real companies to a public audience. Survey data provide insights into the effectiveness of social media as a tool for teaching core course concepts.